Association between microRNA 671 polymorphisms and the susceptibility to soft tissue sarcomas in a Chinese population - Zhang, Peng; Li, Xinling; Huang, Lingling; Hu, Fulan; Niu, Xiaoying; Sun, Yang; Yao, Weitao (Frontiers in Oncology, 2022)
This study evaluated the association between the microRNA (miRNA) gene polymorphisms and the susceptibility to soft tissue sarcomas (STSs). In this case–control study, DNA was extracted from leukocytes in peripheral blood, which was collected from 169 STSs patients and 170 healthy controls. Three SNPs for miR-210, five SNPs for miR-206, two SNPs for miR-485, two SNPs for miR-34b, two SNPs for miR-671, and three SNPs for miR-381 were investigated and genotyped using a Sequenom Mass ARRAY matrix-assisted laser desorption/ionization-time of flight mass spectrometry platform. Unconditional logistic regression analysis was used to analyze the association between miRNA gene polymorphisms and the susceptibility to STSs. The results showed that miR-671 rs1870238 GC + CC (OR = 1.963, 95% CI = 1.258–3.064, P = 0.003) and miR-671 rs2446065 CG + GG (OR =1.838, 95% CI = 1.178–2.868, P = 0.007) may be genetic risk factors for STSs after adjustment for age and smoking. Therefore, this study suggests that individuals carrying the GC + CC genotype for miR-671 rs1870238 or the CG + GG genotype for miR-671 rs2446065 are susceptible to STSs.